Face-Threating Behavior (FTA) Analysis on “Supernanny” Show: A Pragmatics Study - Robertus Dewa Brata Krisantoaji; Heri Heryono (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The purpose of this study is to analyze the occurrence of FTA (face-threating behavior) in the data and the FTA strategy used. A descriptive qualitative research method was used for the analysis. The data used was obtained from Supernanny (a British TV show). The four free trade zone strategies identified from the data are Bold - On Record, Off Record, Positive Politeness, and Negative Politeness. Bald-On Record has a 50% incidence, so positive politeness is 40%, off the record is 46%, and negative politeness is 16%. According to the results of this analysis, FTA was found to predominate in 86% of incidences, with the most commonly used strategy being the most common coming soon strategy with a 50% percentage.